A milk casein hydrolysate‐derived peptide enhances glucose uptake through the AMP‐activated protein kinase signalling pathway in skeletal muscle cells. Issue 2 (3rd January 2021) - Iwasa, Masayo; Takezoe, Shiina; Kitaura, Naoko; Sutani, Takatoshi; Miyazaki, Hidetoshi; Aoi, Wataru
Abstract : New Findings: What is the central question of this study? How do common active ingredients contained in both Lactobacillus helveticus ‐fermented milk and milk casein hydrolysate (MCH) enhance glucose metabolism by skeletal muscle? What is the main finding and its importance? MCH enhanced glucose uptake in skeletal muscle cells by stimulating AMP‐activated kinase, but not insulin, signalling. Moreover, the MCH‐derived specific peptide Ile‐Pro‐Pro mimicked this effect, suggesting a mechanism for MCH‐induced metabolic improvement. Abstract: Improvement of glucose metabolism in the skeletal muscle has a key role in exercise performance and prevention of metabolic diseases. In our previous study, we showed that intake of milk casein hydrolysate improves glucose metabolism in humans, but the mechanism of action was not elucidated. In this study, we aimed to investigate the mechanism of action of milk casein hydrolysate and its derived peptides on glucose uptake and glucose metabolic signalling in cultured skeletal muscle cells. Differentiated C2C12 myotubes were used for the experiments. The differentiated cells were incubated with milk casein hydrolysate, valine–proline–proline and isoleucine–proline–proline. Subsequently, the rate of 2‐deoxy‐glucose uptake and the phosphorylation levels of insulin‐dependent and ‐independent signalling factors were examined. We found that the rate of 2‐deoxy‐glucose uptake in both milk casein hydrolysate and isoleucine–proline–proline‐treated cells was higher than that in the control cells. Immunoblotting assays showed that the phosphorylation levels of AMP‐activated protein kinase, a rate‐limiting factor in insulin‐independent signalling, and of liver kinase B1, an upstream factor of AMP‐activated protein kinase, in both milk casein hydrolysate and isoleucine–proline–proline‐treated cells were higher than those in the control cells. Such significant effects were not observed after treatment with valine–proline–proline. Moreover, the insulin‐dependent signalling was not significantly affected under the different conditions. The findings of our study suggest that milk casein hydrolysate enhances glucose uptake by activating insulin‐independent AMP‐activated protein kinase signalling in skeletal muscle cells, which might be mediated by a milk casein hydrolysate‐derived peptide, namely, isoleucine–proline–proline. Abstract :